Effects of aerobic treadmill exercise on the bone turnover in obese male mice - Du, Yuxiang; Liu, Guanghua; Zhang, Limei; Lin, Haiqi; Gao, Bo; Zhang, Lingli (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThis study aims to investigate the effects of aerobic exercise on the bones of obese male mice induced by a high-fat diet and determine the related mechanisms. Results will provide a reference for exercise-related recommendations in the early adulthood of rodents.MethodsSixty male C57BL/6 mice were raised to 5 weeks of age and then stratified randomly by body weight into a normal diet group and a high-fat diet group for a 12-week dietary intervention. After 12 weeks, successfully modeled obese male mice were stratified randomly by body weight into an obese control group and an obese exercise group. Twenty mice from the normal diet group were stratified randomly by body weight into a control group and an exercise group. A 10-week aerobic treadmill exercise intervention was conducted, and the feed administered to each group was not changed.ResultsHigh-fat diet-induced obesity causes abnormalities in body weight, blood glucose, and lipid metabolism in mice, inhibits bone formation, promotes bone resorption, and leads to decreased bone mass in obese male mice.ConclusionThese findings are mainly related to the inhibition of the WNT signaling pathway and the dysregulation of adipokines. Aerobic exercise can effectively reduce the body weight of obese male mice and alleviate abnormalities in glucose and lipid metabolism. To some extent, it also alleviates the inhibition effect of obesity on WNT pathway signaling, promotes bone formation, and inhibits bone resorption.